EXAMINING ASEAN OUR EYES DEALING WITH REGIONAL CONTEXT IN COUNTER TERRORISM, RADICALISM, AND VIOLENT EXTREMISM - Wilujeng, Nila Febri; Risman, Helda (PEOPLE: International Journal of Social Sciences, 2020)
ASEAN currently contends with the global context emerging dynamically which brings about multidimensional challenges and threats. Dealing with this circumstances, ASEAN member states strengthen its capacity by enhancing regional cooperation and strategic information exchange among ASEAN member states so-called ASEAN Our Eyes. This initiative adopted for the sake of forestalling any possible threat posed by terrorism, radicalism, and violent extremism through timely strategic information exchange among ASEAN member states. This study will be analyzed with Regional Security Complex and International Cooperation theories to examine ASEAN Our Eyes based on its Terms of Reference (TOR). By using a qualitative method, the result of this study portrays that ASEAN Our Eyes is able to undermine the gaps in the realm of strategic information exchange in monitoring the movement of foreign terrorist fighters, violent extremists, radicals, and crime-terror nexus. However, it remains premature as a strategic measure to encounter those threats in the upcoming years.